2016
DOI: 10.1186/s12885-016-2634-1
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulating epithelial tumor microenvironment in vitro using three dimensional tri-culture of human epithelial, endothelial, and mesenchymal cells

Abstract: BackgroundThree-dimensional (3-D) cultures of cancer cells can potentially bridge the gap between 2-D drug screening and in vivo xenografts. The objective of this study was to characterize the cellular and extracellular matrix characteristics of spheroids composed of human lung epithelial cells (epi), pulmonary vascular endothelial (endo) cells, and human marrow-derived mesenchymal stems cells (MSCs).MethodsSpheroids composed of epi/endo/MSCs, termed herein as synthetic tumor microenvironment mimics (STEMs), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 54 publications
(66 reference statements)
4
60
0
1
Order By: Relevance
“…The modular setup of 4DGG allows several degrees of freedom, namely: 1) the shape of the gradient can be varied by altering the dimensions of the channel in the ISE, 2) since cells are introduced into the channel in the ISE channel as a dispersion in a gel, several cell types – including multicellular spheroids – can be studied at various densities and simultaneously; using various reporter systems, and furthermore, the mechanical property of the gel microenvironment can be varied independently from the aforementioned variables to investigate mechanobiology paradigms, and 3) since the gelatin SSE is independently configured and compatible with a variety of soluble signals, it opens up the possibility of studying a variety of signaling scenarios. Since the 4DGG is based on passive diffusion which is more physiological than other means of transport, it eliminates shear‐related artifacts in cell behavior that could confound analysis and hence offers a valuable alternative to microfluidic devices .…”
Section: Discussionmentioning
confidence: 99%
“…The modular setup of 4DGG allows several degrees of freedom, namely: 1) the shape of the gradient can be varied by altering the dimensions of the channel in the ISE, 2) since cells are introduced into the channel in the ISE channel as a dispersion in a gel, several cell types – including multicellular spheroids – can be studied at various densities and simultaneously; using various reporter systems, and furthermore, the mechanical property of the gel microenvironment can be varied independently from the aforementioned variables to investigate mechanobiology paradigms, and 3) since the gelatin SSE is independently configured and compatible with a variety of soluble signals, it opens up the possibility of studying a variety of signaling scenarios. Since the 4DGG is based on passive diffusion which is more physiological than other means of transport, it eliminates shear‐related artifacts in cell behavior that could confound analysis and hence offers a valuable alternative to microfluidic devices .…”
Section: Discussionmentioning
confidence: 99%
“…However, no increased drug resistance in the 3D models was obtained when compared to standard 2D co‐cultures. In fact, only some concentrations showed a prevailing difference between models, with the 3D model presenting always an increased cellular viability in comparison to the 2D model …”
Section: Cancer‐mscs Co‐culture Relevance In 3d In Vitro Tumor Modelsmentioning
confidence: 93%
“…In vivo studies in mice demonstrated the capacity of ectopically injected BM‐MSCs of migrating toward xenografts of human pancreatic cancer, in which BM‐MSCs lead to an increase in the number of CD31+ early vascular structures, an event that directly correlates with the density of tumor vascularization, as was observed, with tumors with twice the vascularization of those in obtained in controls . Another tri‐culture was performed by Lamichane and co‐workers, 2016, in which A549 cells were co‐cultured with human pulmonary microvascular endothelial cells and BM‐MSCs . The tracking of the different cellular populations was accomplished through transfection with lentiviral particles encoding red fluorescent (RFP) and green fluorescent (GFP) transgene reporters, and followed for 15 days.…”
Section: Cancer‐mscs Co‐culture Relevance In 3d In Vitro Tumor Modelsmentioning
confidence: 96%
“…3D tumor spheroids are aggregates of cells that can be grown in suspension on minimally adherent surfaces. Tumor spheroids have been reproducibly used for decades and can be composed of tumor cells only or can contain other cell types such as fibroblasts, mesenchymal stromal cells, and endothelial cells [36]. Depending on the source of cells (primary or cell line), tumors can form tight/dense spheroids, compact aggregates or loose aggregates depending on the cells' adhesive properties or epithelial vs mesenchymal origin [37].…”
Section: Three-dimensional Tissue Culturementioning
confidence: 99%
“…Overall, 3D spheroid cultures mimic the physical tumor microenvironment, including cell-to-cell interactions, but fail to fully recapitulate the ECM and growth factors present in solid tumors. While tumor spheroids have been generated with other cell types such as stromal and endothelial cells [36,49], studies investigating OAds in these models have yet to be completed.…”
Section: Three-dimensional Tissue Culturementioning
confidence: 99%